CD47;Rag2;IL-2rγ triple knock-out mice pre-conditioning with busulfan could be a novel platform for generating hematopoietic stem cells engrafted humanized mice - Kim, Kang-Hyun; Lee, Sang-wook; Baek, In-Jeoung; Song, Hye-Young; Jo, Seon-Ju; Ryu, Je-Won; Ryu, Seung-Hee; Seo, Jin-Hee; Kim, Jong-Choon; Heo, Seung-Ho (Frontiers in Immunology, 2024)
Humanized mouse models to recapitulate human biological systems still have limitations, such as the onset of lethal graft-versus-host disease (GvHD), a variable success rate, and the low accessibility of total body irradiation. To address these limitations, we generated human CD34+ hematopoietic stem cell engrafted humanized mice using a novel mouse strain, NOD-CD47 null Rag2 null IL-2rγ null (RTKO) mice pre-conditioned with total body irradiation or busulfan (BSF) injection, and compared them with NOD-Rag2 null IL-2rγ null mice. For a long period from 16 to 40 weeks post transplantation, the percentage of hCD45 was mostly maintained above 25% in all groups, and it was sustained the longest and highest in the RTKO BSF group. Reconstruction of human leukocytes, including hCD3, was also most prominent in the RTKO BSF group. Only two mice died before 40 weeks post transplantation in all groups, and there were no life-threatening GvHD lesions except in the dead mice. The occurrence of GvHD has been identified as mainly due to human T cells infiltrating tissues and their related cytokines. Based on these results, humanized mouse models under all conditions applied in this study are considered suitable models for long-term experiments. Especially, RTKO mice pretreated with BSF are expected to be a valuable platform for various immune research fields, including cancer immunotherapy, virology, and transplantation.